2013
DOI: 10.1260/1369-4332.16.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Strategy and Parametric Study of Cable-Stayed-Suspension Bridges

Abstract: This paper presents a systematic analysis strategy for cable-stayed-suspension bridges. A four-step approach for the determination of the reasonable finished dead load state is established, focusing on the optimization of the tension forces and shapes of all cables. The critical distribution of the traffic load is imposed on the bridge simultaneously with the dead load to calculate its nonlinear effect. Taking the finished dead load state as the initial state, the nonlinear effect of each load in the service s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…They advocated for exploring global 3D temperature effect numerical simulations and optimizing the placement of temperature sensors based on the boundary conditions required by the numerical simulations. Shan et al (2023aShan et al ( , 2023b established a global three-dimensional finite element model of the Qingzhou Bridge. They used transient heat conduction analysis to calculate the detailed temperature distribution throughout the entire bridge for all four seasons which found that the horizontal displacement of the bridge towers and the longitudinal displacement of the bridge ends are primarily affected by the average temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They advocated for exploring global 3D temperature effect numerical simulations and optimizing the placement of temperature sensors based on the boundary conditions required by the numerical simulations. Shan et al (2023aShan et al ( , 2023b established a global three-dimensional finite element model of the Qingzhou Bridge. They used transient heat conduction analysis to calculate the detailed temperature distribution throughout the entire bridge for all four seasons which found that the horizontal displacement of the bridge towers and the longitudinal displacement of the bridge ends are primarily affected by the average temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the Qingma suspension bridge spanning 2132 meters, Xia et al (2013) combined numerical analysis with field monitoring to study temperature distribution and response. Shan et al (2023aShan et al ( , 2023b analyzed the global temperature field of a long-span cable-stayed bridge across different seasons, integrating heat transfer analysis and field monitoring data. They proposed a method for uniformly calculating temperature responses, highlighting the significant impact of temperature changes in tension cables, where the temperature stress ratio to the constant load stress of the main girder reached 96%.…”
Section: Introductionmentioning
confidence: 99%
“…The structural members in the cable-stayed suspension bridge are introduced in Figure 1 . Compared with suspension bridges, the cable-stayed suspension bridges have higher structural rigidity [ 1 , 2 ]. Compared with cable-stayed bridges, the cable-stayed suspension bridge provides better stability because of the lower compressive force caused by bridge decks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has a lower cost than a suspension bridge with the same bridge span. Hence, the cable-stayed suspension bridge is an excellent solution for long-span bridges across the sea for structural, economic, and practical reasons [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation